AB0231 Physician visual analog scale estimates for damage are higher than for inflammation in patients with osteoarthritis and also in patients with rheumatoid arthritis at all levels of clinical severity according to rapid3. (15th June 2017) - Castrejon, I; Chua, J; Block, JA; Pincus, T
Abstract : Background: A visual analog scale (VAS) to estimate the patient's global status (DOCGL) often is the most efficient of all 7 RA core data set measures to distinguish active from control treatments in clinical trials 1 . DOCGL is designed to assess inflammatory activity, but it may be influenced variably in different doctors by irreversible joint damage and/or distress. Therefore, 3 additional 0–10 VAS have been developed to estimate levels of inflammation, damage, and distress that may impact DOCGL. Objectives: To analyze 4 estimates for overall global, inflammation, damage and distress according to 4 RAPID3 (routine assessment of patient index data) severity categories in patients with RA or OA. Methods: Patients seen at one academic clinical setting are assigned 4 0–10 VAS estimates: overall DOCGL, inflammation (reversible), damage (irreversible), and distress (symptoms explained by neither inflammation nor damage, eg, fibromyalgia). All patients complete a self-reported MDHAQ questionnaire as part of routine care. The MDHAQ includes 0–10 scores for physical function (FN), pain (PN), patient global estimate (PATGL), compiled into a 0–30 RAPID3. Patients with a primary diagnosis of RA or OA according to their rheumatologists were included. The percentage of RA and OA patients in each RAPID3 severity category was compared according to mean DOCGL and the 3 subscale estimates using chi-square and ANOVA. Results: The study included 232 patients with RA and 274 with OA. Patients with OA were older than RA patients (66.5 versus 57.3, p<0.001) and had higher scores for RAPID3 (14.4 vs 11.7, p<0.001). A higher percentage of patients with OA had high RAPID3 severity compared with RA patients (66% vs 48%, p<0.001) (Table). DOCGL and each subscale estimate were higher according to each of 4 RAPID3 categories from remission to high severity in RA and OA (Table). The level of inflammation was higher in RA than in OA, but estimates for damage higher in OA than RA. However, estimates for damage were higher than for inflammation in RA in each RAPID3 category. Conclusions: Physician VAS for inflammation, damage, and distress may supplement the overall physician global estimate as quantitative physician estimates of reversible findings, irreversible findings, and distress to support clinical management decisions. Estimates of joint damage are higher in OA than in RA, although higher than estimates of inflammation in both RA and OA, in patients in all 4 RAPID3 severity categories. References: Pincus T, et al. Clin Exp Rheumatol 2014; 32 (Suppl. 85): S47-S54. Disclosure of Interest: I. Castrejon: None declared, J. Chua: None declared, J. Block: None declared, T. Pincus Shareholder of: Health Report Services, Inc